Customer Satisfaction, Social Influence, and Facilitating Conditions Affecting Use Behavior in Ride-Hailing - Erwin Sutomo; Sulistiowati Sulistiowati; Vivine Nurcahyawati; Martinus Sony Erstiawan; Ayuningtyas (Universitas Dinamika, 2025)
The rapid expansion of online ride-hailing services has transformed urban mobility; however, sustaining user engagement remains a major challenge due to the interplay of psychological and technical factors. Despite widespread adoption, the determinants influencing users’ continued use of such applications remain inconsistent and not fully understood. Therefore, this study examines the effects of Customer Satisfaction (CS), Social Influence (SI), and Facilitating Conditions (FC) on Use Behavior (UB) of online transportation applications, with Behavioral Intention (BI) as a mediating variable. The research was conducted in Surabaya with 150 active users of online ride-hailing services, and data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that FC significantly affects both BI and UB, while CS and SI have significant positive effects on BI but not directly on UB. Moreover, BI is identified as the strongest predictor of UB and acts as a significant mediator in the relationships CS → BI → UB, SI → BI → UB, and FC → BI → UB. These results highlight the central role of intention in linking psychological and technical factors to actual use behavior. The study suggests that service providers enhance customer satisfaction, utilize social influence, and strengthen facilitating conditions to sustain user engagement.